Unveiling hotspots of emerging research in the miRNA-related mechanism underlying cancer through comprehensive bibliometric analysis with implications for precision medicine and non-invasive diagnostics - Zhang, Zhirui; Song, Wenhuan; Chen, Wenyu; Cui, Wenze; Chen, Wenyi; Zhang, Qinheng; Ji, Wenwen; Wang, Yinglin; Wang, Jiayi; Yu, Wenhao; Yu, Mingkun; Hao, Tao; et al. (Frontiers in Oncology, 2025)
Background and objectiveMicroRNAs (miRNAs) are implicated in cancer by exerting roles in tumor growth, metastasis, and even drug resistance. The general trends of miRNA research in diverse cancers are not fully understood. In this work, miRNA-related research in colorectal cancer, prostate cancer, leukemia, and brain tumors was analyzed in search of key research trends with clinical potential.MethodsA bibliometric analysis of articles, spanning from 2014 to 2024, was carried out with the major focus laid on four types of cancers. The Co-citation network analysis, keyword bursts, and the collaborative pattern were done in VOSviewer and CiteSpace, respectively.ResultsColorectal cancer had the highest publication volume, with research primarily focusing on gene expression, extracellular vesicles, and non-coding RNAs. Prostate cancer showed a shift toward clinical applications, while leukemia and brain tumor research, though less extensive, highlighted miRNA’s potential in early diagnosis and treatment. Co-citation analysis identified emerging research collaborations and key contributors.ConclusionmiRNA plays a pivotal role in cancer diagnosis, biomarker development, and therapeutic interventions. With advancements in non-invasive diagnostics and personalized medicine, miRNA offers significant potential for clinical applications. Future research should focus on miRNA’s role in drug resistance and combination therapies to accelerate its clinical translation.